Al-lugha al-fuṣḥâ : archéologie d’un concept « idéolinguistique » - Pierre Larcher (Revue des Mondes Musulmans et de la Méditerranée)
Every French Arabicist knows that the expression al-lugha al-fuṣḥâ designates the Arabic variety that they themselves call Classical Arabic. But today, we have forgotten this expression comes from and what was its original meaning. In the first part of this paper, entitled « Theology and philology of Medieval Islam » we will recall that the expression is primarily a rewritting of ’afṣaḥ al-lughât al-‘arabiyya (« the most polished Arabic way of speaking »), which designs the lughat Quraysh, to whom the Quranic language is identified on a scriptural basis and not on a linguistic one. In a second part, entitled « Ideology and Linguistics at the Modern Period » we examine how and when this medieval expression was revitalized to design what a famous Arab nationalist thinker described as a lugha muwaḥḥida wa-muwaḥḥada (« a unifying and unified language»). In both cases, we will point out that the concept is at the crossroad of ideology and linguistics; a reason why we suggest to define it as ideolinguistic, on the model of sociolinguistic.